2015
DOI: 10.1016/j.semcancer.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment abnormalities and lymphomagenesis: Immunological aspects

Abstract: Innate and adaptive immune cells within the microenvironment identify and eliminate cells displaying signs of malignant potential. Immunosurveillance effector Natural Killer (NK) cells and Cytotoxic T Lymphocyte (CTLs) identify malignant cells through germline receptors such as NKG2D and in the case of CTLs, presentation of antigen through the T cell receptor. Manipulation of immunosurveillance through altered tumor-identifying ligand expression or secretion, resistance to cytotoxicity, or compromised cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 127 publications
(146 reference statements)
0
19
0
Order By: Relevance
“…Studies performed in EBV+HL showed a similar increment of immunosuppressive cytokine genes (IL-10 and TGFβ) expression. IL-10 is secreted by HRS cells in HL and also by tumor cells and associated macrophages in BL 36 . In our series, we found that IL-10 is produced both by tumor cells and the reactive microenvironment, as shown by IHC, although no statistically significant difference was detected according to EBV status.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in EBV+HL showed a similar increment of immunosuppressive cytokine genes (IL-10 and TGFβ) expression. IL-10 is secreted by HRS cells in HL and also by tumor cells and associated macrophages in BL 36 . In our series, we found that IL-10 is produced both by tumor cells and the reactive microenvironment, as shown by IHC, although no statistically significant difference was detected according to EBV status.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of natural killer cells (NK cells) and natural killer T cells in the majority of solid tumors often means a good prognosis [1]. Within the TME, NK cells and CTLs are capable of recognizing malignant cells owing to the expression of NKG2D and T cell receptors, respectively [45]. Monocytes are recruited from the circulation and differentiate into macrophages within the TME where stromal and tumor cells provide chemokines and growth factors mainly CCL2, CSF1, CCL18, CCL20, CXCL12, and VEGF-A [46].…”
Section: Cells Of the Adaptive Immune System In Tmementioning
confidence: 99%
“…they reduce secretion of proinflammatory IFN-g and TNF-a by Th 1 cells and of IL-17 by Th 17 cells. Such ac-tivities promote carcinogenesis via inhibiting secretion of antitumor mediators [33]. TGF-b is a cytokine that inhibits excessive proliferation and repressor genes encoding for cytotoxic mediators, including perforin, granzymes A and B and IFN-g [34].…”
Section: Immune Response Modulation By H Pylorimentioning
confidence: 99%
“…This happens until carcinogenic cells become resistant to the stimuli initiated by this mediator, for example by the increased activity of mammalian target of rapamycin (mTOR), which makes carcinogenic cells insensitive to TGF-b-mediated antiproliferative activity [35]. In such situations, elevated TGF-b level is beneficial for lymphoma development because it disrupts cytotoxic and proapoptotic activity to tumor-altered cells [33]. In an in vivo mouse model, Craig et al demonstrated the ability of Helicobacter spp.…”
Section: Immune Response Modulation By H Pylorimentioning
confidence: 99%